Housing Prices in British Columbia: Quantifying the Zoning Effect - Zemp, Nathan (Canadian Planning and Policy / Aménagement et politique au Canada, 2025)
British Columbia (B.C.)’s housing prices have increased dramatically in recent times, and one potential explanation is municipal zoning bylaws limiting housing supply. However, the effect of zoning on housing prices in aggregate has not yet been studied in B.C. In this study, I use a regression analysis, adapted from an Australian study, to estimate the “zoning effect”: the extent to which zoning controls increase the sale prices of dwellings. I calculate this effect for detached homes in 30 of B.C.’s largest cities and towns, and for apartments in the Metro Vancouver region. I look at how home prices changed between 2016 and 2022, and the extent to which the zoning effect influenced this trend. Finally, I evaluate the potential of government initiatives aimed at decreasing the cost of housing through the lens of the zoning effect, and suggest possible future courses of action.